This is a homework problem I’m trying to solve but I can’t seem to solve Q1b without using the theorem.

enter image description here

I am also given the fact that


I’ve tried using the trace-expectation trick but to no avail. Assuming $y\sim N(0,I)$, $$\begin{align*} var(y’Ay) &=E[(y’Ay-tr(A))^2]\\ &=E(y’Ayy’Ay)-tr(A)^2\\ &=E(tr[y’Ayy’Ay])-tr(A)^2\\ &=E(tr[Ayy’Ayy’])-tr(A)^2\\ &=tr(E[Ayy’Ayy’])-tr(A)^2\\ &=tr(AE[yy’Ayy’])-tr(A)^2 \end{align*} $$ Then I’m stuck.


Suppose $A=((a_{ij}))$ and $y=(y_1,y_2,\ldots,y_n)'\sim N(0,I_n)$, so that $y_i$s are i.i.d standard normal.

You already have $\operatorname E[y'Ay]=\operatorname{tr}(A)$ by the result you quoted (discussed here).

For the variance, you can simply use $$\operatorname{Var}(y'Ay)=\operatorname E[(y'Ay)^2]-(\operatorname E[y'Ay])^2\tag{1}$$

To compute the first expectation, we write the quadratic form as $y'Ay=\sum_{i,j}a_{ij}y_iy_j$ to get $$(y'Ay)^2=\sum_{i,j,k,l}a_{ij}a_{kl}y_iy_jy_ky_l \tag{2}$$

Now observe that $$\operatorname E[y_iy_jy_ky_l]=\begin{cases}3&,\text{ if }i=j=k=l \\ 1&,\text{ if }i=j,k=l;i=k,j=l;i=l;j=k \\ 0&,\text{ otherwise }\end{cases}$$

Therefore taking expectation on both sides of $(2)$,

$$\operatorname E[(y'Ay)^2]=3\sum_i a_{ii}^2+\sum_i\left(\sum_{k\ne i}a_{ii}a_{kk}+\sum_{j\ne i}a_{ij}^2+\sum_{j\ne i}a_{ij}a_{ji}\right)\tag{3}$$

Keeping in mind that $A$ is symmetric, you have $\operatorname{tr}(A^2)=\sum_{i,j}a_{ij}^2$.

It is now straightforward to see that $(3)$ reduces to $$\operatorname E[(y'Ay)^2]=(\operatorname{tr}(A))^2+2\operatorname{tr}(A^2)$$

From $(1)$ you get the desired result $$\boxed{\operatorname{Var}(y'Ay)=2\operatorname{tr}(A^2)}$$

You can now try to generalize this to the case $y\sim N(0,\Sigma)$ and hence to $y\sim N(\mu,\Sigma)$.


  • Linear Regression Analysis by Seber and Lee.
  • $\begingroup$ Since $A$ is symmetric, the easier way to find the variance directly for the $N(0,I_n)$ case is to use spectral decomposition to write $A=P'\Lambda P$ for some orthogonal $P$ and $\Lambda=\operatorname{diag}(\lambda_1,\ldots,\lambda_n)$ where $\lambda_i$ are eigenvalues of $A$. Then $y'Ay=x'\Lambda x=\sum_{i=1}^n \lambda_i x_i^2$ with $x=Py\sim N(0,I_n)$. $\endgroup$ Jul 14 '20 at 16:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.